Do higher childcare subsidies improve parental well-being? Evidence from Québec's family policies - Abel Brodeur; Marie Connolly (Institute for the Study of Labor (IZA), 2012)
In this paper, we investigate the effect of a change in childcare subsidies on parental subjective well-being. Starting in 1997, the Canadian province of Québec implemented a generous program providing 5-a-day childcare to children under the age of 5. By 2007, the percentage of children attending subsidized day care had tripled and mothers' labor force participation had increased substantially. Objectively, more labor force participation is seen as a positive improvement, bringing with it higher income, independence and bargaining power. Yet a decrease in women's subjective well-being over previous decades has been documented, perhaps due to a Second Shift effect where women work more but still bear the brunt of housework and childrearing (Hochschild and Machung, 1989). Using data from the Canadian General Social Survey, we estimate a triple-differences model using differences pre- and post- reforms between Québec and the rest of Canada and between parents with young children and those with older children. Our estimates suggest that Québec's family policies led to a small decrease in parents' subjective well-being. Of note, though, we find large and positive effects for poor household families and high school graduates and negative effects for middle household income families. We find similar negative effects on life satisfaction for both men and women, but different effects on satisfaction with work-life balance. This suggests that fathers' life satisfaction could be influenced by their wives' labor supply while their work-life balance is not.
Keywords: I31; J20; J28; 330; childcare; labor supply; subjective well-being; life satisfaction; happiness; work-life balance